Parental-reported neurodevelopmental issues in Loeys-Dietz syndrome. (December 2018) - Collins, R.T.; Flor, J.M.; Tang, X.; Bange, J.M.; Zarate, Y.A.
Abstract: Background: Loeys-Dietz syndrome (LDS) is a congenital multisystem disorder affecting the cardiovascular and musculoskeletal system. Limited data have reported neurodevelopmental (ND) issues in LDS. Aims: To determine the extent of ND issues in patients with LDS. Methods: A prospective study was performed of LDS patients or their caregivers. The study included data collected via an online survey of age-specific questions. Standard statistical methods were used for baseline and demographic characteristics, as well as group comparisons. Outcomes: Data were obtained from 67 patients with LDS (54% female). Median age was 14.9 years. Gene mutations included TGFBR1 (39%), TGFBR2 (40%), SMAD3 (7%), and unknown (14%). Motor delays (30%, 18/61) and hypotonia (63%, 37/60) occurred frequently. Physical (62%, 39/62), occupational (41%, 23/56), and speech therapies (34%, 20/58) were common. Feeding issues were common (41%, 23/56). TGFBR1 mutations were more frequent among those with motor delays and feeding issues. Conclusions: Patients with LDS and/or their caregivers report at least one ND problem in most cases, and many require therapies. These data suggest ND disorders should be considered to be part of the phenotype.